Pelayanan Pengaduan Masyarakat Peduli Lingkungan Pada Dinas Lingkungan Hidup Kota Palangka Raya - Sigai, Juniardo Silcher Runting; David, Tommy Ekadino; Bagir, Muhammad; Julianto, Eko; Handayani, Risma Utami; 'ani, Sam; Ichsan, Mochammad; Qamaruzzaman, Muhammad Haris (Universitas Bakti Tunas Husada, 2024)
Palangka Raya City, as the center of government and economic growth in Central Kalimantan, faces serious challenges in waste management. The increasing amount of waste generated by community and industrial activities demands attention and concrete action to maintain cleanliness and environmental sustainability. This community service activity aims to raise public awareness about the importance of proper waste management and to provide facilities for reporting and handling waste. The activities include socialization and counseling about the types of waste, the negative impacts of waste on health and the environment, as well as effective reporting procedures. By providing easily accessible reporting facilities, such as hotlines and mobile applications, it is hoped that the community can play an active role in reporting waste issues they encounter. The expected outcomes of this activity are increased public awareness, an increase in the number of waste reports, and more effective waste management, which in turn will contribute to a cleaner and healthier environment in Palangka Raya City. This community service activity is implemented as part of the Field Work Practice (PKL) of the Integrated School of Management Informatics & Computer (STMIK). This activity is expected to create a culture of shared responsibility in environmental management and support the sustainability efforts initiated by the local government.